Pengaruh Pemberian Murottal Al-Qur’an Terhadap Lama Tidur Bayi Usia 3-6 Bulan - Yesi Ermawati; Rita Riyanti Kusumadewi (Jurnal Anestesi, 2023)
Background : The need for sleep can not only be seen from the aspect of sleep quality but can also be seen from the quantity or long duration of a baby's sleep. If the baby's sleep duration is met properly, the baby's growth and development can be achieved optimally. Nearly 44.2% of babies experience sleep disturbances or sleep problems, so far 72% of parents think it is not a problem, whereas if a baby has sleep problems it will have a negative effect on growth, including vulnerable immunity, as well as changes in the endocrine system. affect the growth of the baby. Currently, various ways of therapy have been carried out so that there is an increase in the baby's sleep duration. One of the safe and accessible therapeutic efforts to increase the baby's sleep duration is using murottal Al-Qur'an. Al-Qur'an murottal therapy can reduce stress hormones, activate natural endorphins, increase feelings of relaxation, and distract from anxiety, anxiety and tension. The surah used is surah Al-Mulk. Objective : To determine the effect of giving Al-Qur'an murottal therapy on the sleep duration of infants aged 3-6 months. Method : This type of research uses a pre-experimental method with a one group pretest-posttest design. The samples obtained from the federar formula were 20 infants aged 3-6 months using the accidental sampling technique. Results : the results of the study using the Wilcoxon test obtained a p value = 0.000 where the value (p <0.005) means that there is an effect of giving Al-Qur'an murottal therapy on the baby's sleep duration. Conclusion: There is an effect of giving Al-Qur'an murottal therapy on the sleep duration of infants aged 3-6 month.